Reliability of the Rubber Tube of Automotive Hydraulic Braking System Under Fatigue Failures Considering Random Variation of Load and the Process of Aging of Material - Larin, O. O.; Potopalska, K. E.; Mygushchenko, R. P. (Islamic Azad University, Iran, 2019)
This paper presents the approach for the assessing of the operational reliability of a multi-layer thick-walled tube made of rubber with textile reinforcement. The analysis of the fatigue accumulation process is carried out within the framework of the concept of the continuum mechanics of damage. The mathematical model, which takes into account the accumulation of damages in case of a random spread of the strength characteristics of the material, as well as the process of stochastic aging for the elastomeric matrix of the composite and possible random variation of the workload has been developed. In this case, the aging process is modelled as a reduction of the endurance limit of the material. In this paper, the mean equivalent strains of the tube and their possible statistical variation in operation have been investigated on the basis of the finite element method. To solve the above problems, a submodeling method has been employed in this work. The probability of non-failure operation of the tube has been determined using the methods and models proposed. The influence of the rate of the aging process on the lifetime of the tube has been estimated.
Keywords: rubber pipe; composite; fatigue; life-time